Pemberdayaan Masyarakat Melalui Optimalisasi Pakan Ayam Kampung Unggul Balitnak (KUB) di Kelompok Wanita Tani Talago Makmur - Amizar, Robi; Wizna, Wizna; Mirzah, Mirzah; Rusli, Ridho Kurniawan; Zurmiati, Zurmiati; Heryandi, Yan; Andika, Romi; Ardika, Fitrah Thyasta; Robi Amizar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
This community service activity aims to optimize the business activities of the Talago Makmur farmer women's group in the Kampung Unggul Balitnak (KUB) Chicken Farming Business. This activity focuses on increasing understanding through optimizing the use of local feed, providing probiotics, and managing maintenance and cultivation. This activity is designed to combine counseling, training, practical demonstrations, monitoring, and evaluation, thereby increasing the percentage of farmers who understand the material. The counseling materials provided include knowledge of feed, ration preparation, and probiotic administration. Feedback from the activity was measured based on questionnaire data to assess the level of knowledge and understanding of group members who participated in the community service activity. The results of this community service activity indicate that the counseling has been carried out effectively, improving farmers' knowledge and practical skills in ration formulation. A new approach focused on optimizing the use of local feed and probiotics was implemented to encourage community empowerment. Twenty group members attended this activity. Activities carried out include counseling sessions, ration preparation training, discussions, data collection from questionnaires, and distribution of assistance for laying hens and feed. Based on the evaluation results, farmers' understanding showed an estimated average increase of around 30% after participating in the counseling and training activities. The conclusion of this community service activity is an increase in understanding of the use of local feed and probiotics, as well as the development of skills among members of the Talago Makmur farmer women's group through the practice of making rations to optimize KUB chicken rations.